2016
DOI: 10.1093/nar/gkw266
|View full text |Cite
|
Sign up to set email alerts
|

GAM: a web-service for integrated transcriptional and metabolic network analysis

Abstract: Novel techniques for high-throughput steady-state metabolomic profiling yield information about changes of nearly thousands of metabolites. Such metabolomic profiles, when analyzed together with transcriptional profiles, can reveal novel insights about underlying biological processes. While a number of conceptual approaches have been developed for data integration, easily accessible tools for integrated analysis of mammalian steady-state metabolomic and transcriptional data are lacking. Here we present GAM (‘g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 31 publications
0
65
0
Order By: Relevance
“…Analysis of metabolite data alone, or in combination with RNA-Seq data by a systems-based algorithm (Sergushichev et al, 2016), revealed widespread differences between WT and Trem2 −/− BMDMs in various metabolic pathways. Compared to WT BMDMs in optimal CSF1, Trem2 −/− BMDMs cultured under the same conditions exhibited: 1) a marked decrease of key intermediates in the synthesis of nucleotides (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of metabolite data alone, or in combination with RNA-Seq data by a systems-based algorithm (Sergushichev et al, 2016), revealed widespread differences between WT and Trem2 −/− BMDMs in various metabolic pathways. Compared to WT BMDMs in optimal CSF1, Trem2 −/− BMDMs cultured under the same conditions exhibited: 1) a marked decrease of key intermediates in the synthesis of nucleotides (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Network analysis was performed as previously described utilizing Shiny GAM (https://artyomovlab.wustl.edu/shiny/gam/) (Sergushichev et al, 2016; Vincent et al, 2015). We considered a network of chemical mappings between carbon atoms in substrates and products for all annotated reactions in KEGG database using RPAIRs entries.…”
Section: Methods Detailsmentioning
confidence: 99%
“…To understand the variation in metabolic gene expression networks between macrophage populations we have reviewed and analyzed Immgen data profiling macrophages in various tissues [31] using network analysis approaches developed in our group [5, 32, 33]. First, we have compared metabolic networks in the non-activated bone-marrow macrophages against non-activated peritoneal macrophages combining all the types of peritoneal macrophages available in Immgen.…”
Section: Metabolic Gene Expression and Macrophage Originmentioning
confidence: 99%
“…The metabolic network was analyzed using the network tool Shiny GAM: integrated analysis of genes and metabolites (https://artyomovlab.wustl.edu/shiny/gam/) (32) to identify interactions between metabolites and DEGs generated by spaceflight and simulated microgravity. The criteria were limited by a fold change >2 and a value of P < 0.05.…”
Section: Methodsmentioning
confidence: 99%